Neuronal and glial growth and development - Rodrigues, Cátia Filipa Patrício (2022)
Abstract The correct development and establishment of connectivity of the nervous system is necessary for complex functions such as learning and memory, locomotion or perception. These developmental and wiring processes of the central and peripheral nervous system (CNS and PNS, respectively) rely on the coordinated growth and communication between neurons, muscle and glia. After development is complete, the nervous system has the capacity to change both pre-and postsynaptic elements in response to changes in synaptic activity –a process called structural plasticity. Defects in morphology and activity-dependentplasticity are a hallmark of several neurodevelopmental and neurodegenerative diseases. Despite all the current knowledge, the molecular players involved in the growth, maintenance and communication between neurons, muscle and glia are far from being understood. In the Drosophilaperipheral nervous system (PNS), axons that descend from the ventral nerve cord and ascending sensory axons, are bundled together in nerves with the support of glial cells that function as insulators, allowing the proper conduction of electrical signals. Some PNS glial cells, such as subperineurial glia and wrapping glia, face the challenge of growing throughout Drosophilalarval stages without proliferation, to ensure proper insulation and axonal support. Despite its importance, how glial cells grow and maintain their shape together with neurons is still poorly understood. In our work we showed that RalA GTPase and the exocyst complex are key regulators of wrapping glia growth in the DrosophilaPNS. Genetic analyses showedthat RalA is required in wrapping glia to regulate its growth and development, possibly by recruiting membrane vesicles via the exocyst complex.RalA and exocyst have already been implicated in the growth of other PNS structure in Drosophila, the postsynaptic structure -subsynaptic reticulum (SSR) of the neuromuscular junction (NMJ). The SSR is a complex set of membranes, which is plastic and shown to grow during development and in response to different levels of synaptic activity. The SSR grows via the recruitment of membrane vesicles that are targeted by RalA/exocyst complex interaction. We identified Rab1 and RabX4 as possible candidates to mediate the growth of SSR via RalA/exocyst complex pathway. VIIIThe work in this thesis aimed to explore and uncover pathways that regulate membrane growth and maintenance of neuronal and glial cells in the DrosophilaPNS. By understanding the pathways and how intracellular trafficking orchestrates the correct targeting of vesicles in a spatially and temporally regulated manner, we were able to better learn the molecular underpinnings that govern neuronal growth in different PNS structures, therefore providing insights into the understanding of what goes wrong in disease.